Antique Gold from Burial Mounds from the Viewpoints of Archaeologists and Art Historians. Two Valid Approaches to Representation of the Archaeological Data in Museums (The Experience of the Hermitage Collection) - Radolitskaya, Yana S. (Actual Problems of Theory and History of Art, 2018)
The Hermitage collection of the Greek and Roman golden artifacts from burial mounds of the Northern Black Sea region is the world’s biggest one among those containing archaeological gold, and at the same time — one of the best collections of antique jewelry. The material can be viewed from two principal points of view. On the one hand, such things are an integral part of an archaeological complex, and they include information about the burial itself and the specificity of the burial rite. Along with this, they present the art and culture of the Greek cities of the North Black Sea Region — their economic, political, and religious life. On the other hand, they are works of art that form our ideas of the history of antique toreutics and of antique art as such. This bilateral character of the golden archaeological material brings about the problem of how to exhibit it at the museum: such objects can be either shown along with other things from the same burial thus making a thorough representation of a complex as a whole, or they can be placed in a chronological, typological or any other row of analogues, notwithstanding the location of their find. Fusing these approaches within an exposition without compromising either of them is impossible. This article summarizes the museum exhibition principles of the Hermitage collection of the Greek and Roman golden artifacts, and proposes the author’s position in the light of the problem discussed here.